Effect of sevoflurane and propofol on acute kidney injury in pediatric living donor liver transplantation - Li, Hongxia; Weng, Yiqi; Yuan, Shaoting; Liu, Weihua; Yu, Hongli; Yu, Wenli (Annals of Translational Medicine, 2019)
Background: Acute kidney injury (AKI) is the primary cause of morbidity and mortality after major abdominal surgery. However, little is known about the effect of anesthetics on the development of AKI after pediatric liver transplantation (LT). This study aimed to compare the effects of propofol and sevoflurane anesthetics on postoperative AKI after LT surgery. Methods: A total of 120 pediatric patients scheduled for pediatric LT were randomly assigned to receive either continuous infusion of propofol or inhalation of sevoflurane. Serum creatinine (Scr), inflammatory medium and oxidative stress factors and renal biomarkers were measured before surgery (T1), 5 min after anhepatic phase (T2), 10 min after ischemia reperfusion (T3), 2 h after ischemia reperfusion (T4), 24 h after surgery (T5), and 3 d after surgery (T6) to evaluate the effects of anesthetics on the development of postoperative AKI. Results: The incidence of AKI was lower in patients receiving sevoflurane than those receiving propofol. The mean arterial pressure was changed slightly in sevoflurane group. The inflammatory factors of interleukin-18, tumor necrosis factor-α, and the levels of neutrophil gelatinase-associated lipocalin (NGAL) were lower in sevoflurane group, while no oxidative stress factors [hydrogen peroxide (H2O2), malondialdehyde and superoxide dismutase)] and interleukin-10 showed differences between the groups. Conclusions: Anesthesia with sevoflurane may be associated with a modest decrease in the incidence of AKI when compared with propofol. Further clarification with relevance to such association is warranted.